Coins of the revolutionary Abdullah bin Muawiya Al-Talebi (127-130 AH / 744-747 AD) (Journal of the College of Basic Education, 2022)
Coins were one of the most important media means for Muslim Arabs, and perhaps poetry was also one of the media means, and in the various Islamic eras, everyone who revolted against the authority used coins as messages that reached the various segments and sects of the Islamic society, so they were keen to engrave their slogans and names on them, and most of them were from Silver coins are widely circulated because they are considered an intermediate rail between copper money and gold dinars. Therefore, they were the subject of the care and attention of the revolutionaries. They worked to improve the calligraphy on them for the clarity of their names and slogans, in addition to ridding metals such as gold and silver of impurities and preserving them from fraud, considering the coins they issued as legitimate and confirming their authority over areas under their control.